Abundance of larger mammals in Dinder National Park, Sudan - Mohammed, AA; Bauer, H; Coals, P; Sillero-Zubiri, C (Springer, 2023)
Wildlife is in decline across Africa, particularly in the Sudan-Sahel savanna. An important but little-studied area on the eastern reaches of this biome is Dinder National Park in Sudan. In March 2021, we conducted a distance sampling survey in its ~ 3000 km2 core area around the main Gelego camp, walking a total of 56 line transects over a cumulative distance of 273 km. We calculated the densities of those species with over 20 independent detections using the best-performing model. The most abundant wild species recorded were the olive baboon (25.0 ind/km2) and common warthog (7.3 ind/km2), while the bohor reedbuck (2.1 ind/km2) and oribi (1.9 ind/km2) were the most abundant ungulates. Our survey confirmed the illegal presence of large cattle herds inside Dinder (10.7 ind/km2). The substantial ungulate densities in the core area support regionally important populations of large carnivores, making this one of the best functioning ecosystems in the region. When compared to historical unpublished data from the waterhole and road counts, we detected a declining trend in wildlife numbers over the past 5 decades. We call for improved wildlife monitoring and conservation actions to protect this important ecosystem and for increased efforts to extend effective protection beyond the core area of Dinder.